Slowly digestible starch: a biochemical engineering perspective on functional food development and metabolic health - Raghunathan, Rakesh; Farahnaky, Asgar; Majzoobi, Mahsa; Chandrapala, Jayani; Brennan, Charles; Eri, Rajaraman; Rustagi, Sarvesh; Pandiselvam, R. (Springer, 2025)
Starch, a primary carbohydrate in staple foods, consists of amylose and amylopectin and plays a critical role in human metabolism. However, native starch exhibits limitations in the food industry, such as poor stability and high retrogradation rates, prompting the need for various modification techniques. The global rise in hyperglycemia-related disorders has driven research into strategies for controlling glucose release into the bloodstream. The rate of starch digestion in the small intestine influences blood glucose and insulin responses, with rapidly digestible starch (RDS) causing spikes, while slowly digestible starch (SDS) helps maintain steady levels. Resistant starch (RS), which passes undigested into the large intestine, offers benefits for managing obesity, cardiovascular diseases, and type 2 diabetes. Incorporating SDS into foods can slow gastric emptying and reduce the glycemic index, offering numerous health advantages. Understanding the molecular mechanisms behind SDS is essential given the increasing demand for functional foods. This review explores starch digestion, strategies for enhancing SDS content in foods, its applications, and the associated health benefits, aiming to guide future research in this evolving field.